Ammonia Coordination Introducing a Magnetic Moment in an On‐Surface Low‐Spin Porphyrin1. Issue 17 (19th March 2013) - Wäckerlin, Christian; Tarafder, Kartick; Girovsky, Jan; Nowakowski, Jan; Hählen, Tatjana; Shchyrba, Aneliia; Siewert, Dorota; Kleibert, Armin; Nolting, Frithjof; Oppeneer, Peter M.; Jung, Thomas A.; Ballav, Nirmalya
<x xml:space="preserve">Abstract</x> Amazing ammonia: The molecular spin state of NiII porphyrin, supported on a ferromagnetic Co surface, can be reversibly switched between spin‐off (S=0) and spin‐on (S=1) states upon coordination and decoordination of the gaseous ligand NH3, respectively (see picture). This finding clearly indicates the possible use of the system as a single‐molecule‐based magnetochemical sensor and in spintronics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>